Competitive Strategy Formulation for Lion Parcel Meruyung in Facing Business Competition in The Expedition Service Industry - Albert Apriado; Siti Jahroh; Sufrin Hannan (Green Publisher Indonesia, 2025)
This study examines the competitive positioning of Lion Parcel Meruyung within Indonesia's rapidly expanding courier, express, and parcel (CEP) industry, which has experienced substantial growth amid the e-commerce boom reaching US53 billion in 2023. The research addresses the strategic challenges faced by emerging logistics providers competing against established market leaders (JNE, J&T, Pos Indonesia) and alternative delivery services offered by e-commerce platforms. Employing a comprehensive qualitative methodology, the study gathered primary data through stakeholder interviews and supplemented with secondary data from industry reports and literature. The research framework incorporated multiple analytical tools including PESTLE, Porter's Five Forces, Value Chain Analysis, Competitive Profile Matrix, Internal-External Matrix, SWOT Analysis, Grand Strategy Analysis, and Quantitative Strategic Planning Matrix (QSPM). Findings reveal that Lion Parcel Meruyung operates within a favorably opportunistic market landscape while confronting significant competitive threats from alternative delivery services (weighted score 0.322) and established industry players (0.256). Through systematic strategic formulation processes, ten potential strategies were developed and prioritized using QSPM analysis. Four high-priority strategies emerged: express delivery service development (STAS 6.247), strategic hub expansion for instant delivery capabilities (STAS 6.189), integrated e-commerce partnership programs (STAS 6.123), and implementation of tier-based customer loyalty initiatives (STAS 6.104). This research contributes to strategic management literature by demonstrating practical application of comprehensive analytical frameworks in developing competitive strategies for emerging logistics companies in digitally disrupted markets. The findings offer actionable strategic direction for Lion Parcel Meruyung while providing valuable insights for logistics providers facing similar competitive challenges in emerging economies' rapidly evolving e-commerce landscapes.